2013
DOI: 10.1186/1471-2458-13-1140
|View full text |Cite
|
Sign up to set email alerts
|

Parental alcohol misuse and hazardous drinking among offspring in a general teenage population: gender-specific findings from the Young-HUNT 3 study

Abstract: BackgroundParental alcohol misuse may negatively affect drinking behaviours among offspring, but it is unclear to what extent influences are gender-specific and dependent upon the actual drinking behaviour measured. The aim of this study was to investigate whether hazardous drinking among Norwegian teenage boys (N = 2538) and girls (N = 2494) was associated with paternal and maternal alcohol misuse (CAGE).MethodsDefinitions of hazardous drinking among offspring were based on self-reported alcohol consumption (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 53 publications
6
48
1
8
Order By: Relevance
“…To place these results in context, recent reports indicate that Irish adolescents have very high rates of alcohol and substance misuse compared with their peers in the European Union (UNICEF, 2011). Our result that adolescent substance misuse is more common in boys is expected and is reported in many previous studies (UNICEF, 2011;Hibell et al 2012;Haugland et al 2013). Our study was conducted in 2004 and despite drinking alcohol being illegal under the age of 18 years, the results of widespread drinking among teenagers, with 83% reporting having taken alcohol at some time and 68% drinking alcohol each week (Table 2), are similar to those reported by the ISPCC study of almost 10 000 young people aged 12-18 years in 2009 (Mongan, 2011) in which over two-fifths (45%) reported that they currently drink alcohol.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…To place these results in context, recent reports indicate that Irish adolescents have very high rates of alcohol and substance misuse compared with their peers in the European Union (UNICEF, 2011). Our result that adolescent substance misuse is more common in boys is expected and is reported in many previous studies (UNICEF, 2011;Hibell et al 2012;Haugland et al 2013). Our study was conducted in 2004 and despite drinking alcohol being illegal under the age of 18 years, the results of widespread drinking among teenagers, with 83% reporting having taken alcohol at some time and 68% drinking alcohol each week (Table 2), are similar to those reported by the ISPCC study of almost 10 000 young people aged 12-18 years in 2009 (Mongan, 2011) in which over two-fifths (45%) reported that they currently drink alcohol.…”
Section: Discussionsupporting
confidence: 84%
“…Other studies have indicated that maternal alcohol/substance misuse may have a greater effect on the risk of development of alcohol/substance misuse and other adverse outcomes in children than paternal alcohol/substance misuse (Yule et al 2013). On the other hand, the Norwegian Young-HUNT 3 survey (2006)(2007)(2008) showed that both boys and girls with alcohol misusing fathers were more likely to report high levels of alcohol intake compared with others of the same age and gender (Haugland et al 2013). It was only among the girls that high frequency of drunkenness was associated with maternal alcohol misuse.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, it is possible that other types of psychological distress contribute to the development of trauma-related alcohol misuse. Likewise, unhealthy or maladaptive coping strategies in general might be triggered by other problems, such as parental substance misuse, family dysfunction or personality factors, such as neuroticism and low self-esteem, which could indirectly contribute to the development of AUD (Haugland, Holmen, Ravndal, & Bratberg, 2013;Hwang, et al, 2014;Tomaka, Morales-Monks, & Shamaley, 2013). Future studies should further address these aspects, which extend beyond the scope of the present research.…”
Section: Discussionmentioning
confidence: 95%
“…levels that do not lead to treatment, and alcohol use among children (Ryan, Jorm, & Lubman, 2010;Yu, 2003). Most studies have investigated the role of parental alcohol consumption and offspring alcohol use in adolescence and early adulthood (Alati et al, 2014;Haugland, Holmen, Ravndal, & Bratberg, 2013;Latendresse et al, 2008;Mares, van der Vorst, Engels, & Lichtwarck-Aschoff, 2011;Pape, Rossow, & Storvoll, 2015). In two recent review studies, the authors concluded that the research on how children are affected by parental alcohol consumption at lower levels, not associated with severe alcohol-related problems, actually is very limited (Rossow, Felix, Keating, & McCambridge, 2015;Rossow, Keating, Felix, & McCambridge, 2016).…”
Section: Introductionmentioning
confidence: 93%